Integrating lean and agile manufacturing paradigms: a dynamic simulation analysis. (1st January 2013) - Mutingi, Michael
The systems-based integration of lean and agile manufacturing philosophies plays an important role in enhancing the operational performance of manufacturing systems. However, there is need for in-depth understanding of the dynamics involved. In this research, we seek to address this issue by: 1) identifying a set of performance criteria for a typical manufacturing system; 2) developing a system dynamics simulation model for the system; 3) performing experimental 'what-if' simulation analyses, deriving useful managerial implications. By using the system dynamics simulation methodology, we investigate the impact of the application of lean and just-in-time policies on a traditional inventory-focused manufacturing system. System dynamics modelling is used to capture the dynamic causal linkages between different components of the manufacturing system. Different scenarios are generated in order to investigate the dynamics of the system under assumed demand scenarios. The results of the simulation study reveal that manufacturing systems can benefit from the introduction of lean and just-in-time paradigms, depending on the extent to which the necessary structural changes are implemented. The paper concludes by providing useful managerial insights for effective implementation of lean and agile manufacturing paradigms.